2016
DOI: 10.1021/acs.jpcc.6b04405
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Friendly Processing Technology for Engineering Silicon Nanocrystals in Water with Laser Pulses

Abstract: Herein, we demonstrate the customized, environmentally friendly tailoring of nanoparticles and their surface chemistry by short pulsed laser irradiation in liquids. This process allows for the formation of crystalline spherical particles exceeding several hundreds of nanometers in water from colloids of electrochemically etched silicon nanocrystals (Si-NCs), which exhibit quantum confinement effects and room-temperature stable luminescence. In particular, nanosecond (ns) pulsed laser irradiation of the Si-NC/w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 77 publications
2
23
0
Order By: Relevance
“…In acetone, although the TO mode is located at 520.3 cm -1 , the TO peak becomes asymmetric and broader with a full width at half maxi- mum (FWHM) of 4.8 cm -1 , which can be attributed to the formation of p-Si. Even though the substrate obtained by LAL in water has the same TO position as that obtained in acetone (520.3 cm -1 ), the TO mode of LALwater substrate becomes more asymmetric and its width is much broader with a FWHM of 12 cm -1 , in accordance with previous reports 57 . This indicates that the p-Si generated in water has a much broader size distribution than that generated in acetone.…”
Section: Resultssupporting
confidence: 91%
“…In acetone, although the TO mode is located at 520.3 cm -1 , the TO peak becomes asymmetric and broader with a full width at half maxi- mum (FWHM) of 4.8 cm -1 , which can be attributed to the formation of p-Si. Even though the substrate obtained by LAL in water has the same TO position as that obtained in acetone (520.3 cm -1 ), the TO mode of LALwater substrate becomes more asymmetric and its width is much broader with a FWHM of 12 cm -1 , in accordance with previous reports 57 . This indicates that the p-Si generated in water has a much broader size distribution than that generated in acetone.…”
Section: Resultssupporting
confidence: 91%
“…The average laser power was set to be approximately 30 mW while using the repetition rate of 1 kHz. In order to check the efficiency of the laser‐based surface engineering process with simplified experimental conditions and larger absorption profile of chosen wavelength we first compare with our previous works . Similar to our previous studies, we clearly confirmed the trends in stability and an increase in the PL intensity after fsec laser processing after simplified experimental conditions.…”
Section: Methodssupporting
confidence: 81%
“…In addition, plasma‐induced surfactant‐free surface chemistries on SiNCs showed encouraging results in terms of improved quality and stability of the SiNCs . Surfactant‐free femtosecond (fsec) laser‐induced surface‐engineered SiNCs also proved to be highly effective in promoting the separation of SiNCs , which largely contribute to preserve the individuality of the SiNCs during integration into thin films.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction with water has been found to chemically modify silicon nanoparticles, and as a consequence its fluorescence activity has been seen to 'degrade' (Li and Ruckenstein, 2004;Erogbogbo and Swihart, 2007;Erogbogbo et al, 2008). However, blue fluorescence from nanoscale silicon has been frequently observed, and specifically in connection with treatment with water (Švrček et al, 2009a,b;Intartaglia et al, 2012b,a;Alkis et al, 2012;Svrček et al, 2016;Rodio et al, 2016). …”
Section: Blue Fluorescencementioning
confidence: 99%